Dysregulation of immune cells and platelet-monocyte aggregates in chronic thromboembolic pulmonary hypertension - Lu Sun; Haobo Li; Xincheng Li; Yuhan Li; Min Liu; Han Tian; Jixiang Liu; Ran Miao; Yu Zhang; Qiang Huang; Zhu Zhang; Ximei Niu; et al. (Respiratory Research)
Abstract Background Inflammation and immunological dysregulation are involved in the uncommon pulmonary thromboembolism (PTE) consequence known as chronic thromboembolic pulmonary hypertension (CTEPH). Although tissue samples are provided by pulmonary endarterectomy (PEA), accessibility is restricted by its technical complexity. Immune cells found in peripheral blood may provide information on how a disease develops. Methods We developed a 7-color flow cytometry method using 200 µl of peripheral blood to analyze immune cell subpopulations and platelet immune cell aggregates in CTEPH. PEA tissues were used for immunofluorescence validation. We employed correlation analysis and linear regression to examine the relationships between immune cell dysregulation and the severity of CTEPH. Results There were 36 age- and sex-matched healthy controls, 10 patients with other subtypes of pulmonary hypertension (PH) except CTEPH, 20 PTE patients, and 62 CTEPH patients. CTEPH patients had markedly dysregulated immune cell subpopulations. There was an increase in T lymphocytes from 60.59 ± 9.94% to 69.05 ± 4.90% (p < 0.0001) in CTEPH patients. Classical monocytes decreased (87.94 ± 9.93% vs. 82.02 ± 9.92%, p < 0.0001), while non-classical monocytes increased (3.69 ± 5.42% vs. 8.44 ± 5.91%, p = 0.02) in CTEPH patients. The same trend was also observed in PH group. Dysregulated immune cells were primarily localized in thrombus and neointima regions. Platelet-monocyte aggregates (PMAs) and their subpopulations were positively correlated with hemodynamic and ultrasound indicators. PTE patients had greater levels of PMAs than CTEPH patients (p = 0.0007), and these levels decreased during treatment (p = 0.0168). Conclusion Immune cell subpopulations in CTEPH can be efficiently analyzed using the low blood volume flow cytometry approach. Peripheral blood immune cell dysregulation points to an active immune response in CTEPH. Insights into the pathophysiology of CTEPH may be gained by using PMA as a biomarker for assessing the severity and treatment outcomes of CTEPH. However, more research is needed to determine PMA's role in CTEPH for disease diagnosis assessment and pathogenesis.